Specific Leaf Area and Dry Matter Content Estimate Thickness in Laminar Leaves - VILE, DENIS (Ann Bot, 2005)
• Background and Aims Leaf thickness plays an important role in leaf and plant functioning, and relates to a species' strategy of resource acquisition and use. As such, it has been widely used for screening purposes in crop science and community ecology. However, since its measurement is not straightforward, a number of estimates have been proposed. Here, the validity of the (SLA × LDMC)(−1) product is tested to estimate leaf thickness, where SLA is the specific leaf area (leaf area/dry mass) and LDMC is the leaf dry matter content (leaf dry mass/fresh mass). SLA and LDMC are two leaf traits that are both more easily measurable and often reported in the literature. • Methods The relationship between leaf thickness (LT) and (SLA × LDMC)(−1) was tested in two analyses of covariance using 11 datasets (three original and eight published) for a total number of 1039 data points, corresponding to a wide range of growth forms growing in contrasted environments in four continents. • Key Results and Conclusions The overall slope and intercept of the relationship were not significantly different from one and zero, respectively, and the residual standard error was 0·11. Only two of the eight datasets displayed a significant difference in the intercepts, and the only significant difference among the most represented growth forms was for trees. LT can therefore be estimated by (SLA × LDMC)(−1), allowing leaf thickness to be derived from easily and widely measured leaf traits.